Мефодий Буслаев. Лестница в Эдем: [повесть] / Дмитрий Емец - Емец Дмитрий Александрович (Мефодий Буслаев, 2008)
Экземпляры: (20200218) / Инвентарный номер: 33694 / Цена: 139.50 / Сис.шифр: Р2 / Авт.знак: Е 60 / ГРНТИ: 17 / ББК: 84(2Рос=Рус)6